A simple shear deformation theory for thermo-mechanical behaviour of functionally graded sandwich plates on elastic foundations. (March 2015) - Taibi, Fatima Zahra; Benyoucef, Samir; Tounsi, Abdelouahed; Bachir Bouiadjra, Rabbab; Adda Bedia, El Abbas; Mahmoud, SR
This paper deals with the thermo-mechanical deformation behaviour of shear deformable functionally graded sandwich plates resting on a two-parameter (Pasternak model) elastic foundation. By dividing the transverse displacement into bending and shear parts, the number of unknowns and governing equations of the present theory is reduced, and hence, makes it simple to use. The presented theory is variationally consistent, does not require shear correction factor and gives rise to transverse shear stress variation such that the transverse shear stresses vary in hyperbolic manner across the thickness satisfying shear stress-free surface conditions. A power-law distribution for the mechanical characteristics is adopted to model the continuous variation of properties from those of one component to those of the other. The sandwich plate faces are made of isotropic, two-constituent (ceramic–metal) material distribution through the thickness. The core layer is still homogeneous and made of an isotropic metal material. Several kinds of non-symmetric sandwich plates are presented. The governing equations and boundary conditions are derived using the principle of virtual displacements. Numerical results of the present simple shear deformation theory are presented to show the effect of material distribution and foundation parameters on the deflections and stresses. A wide variety of results is presented for the static response of sandwich plates under thermo-mechanical loads.